Investigation on the supercritical water cooled nuclear reactor - Min, Aung Myat Maw (2015)
In this report, Supercritical Water Cooled Nuclear Reactor (SCWR) is mainly discussed and compared it with the other nuclear reactors for its advantages and disadvantages. It is one of six types Gen-IV nuclear reactor designs selected by the international forum for R&D. It is the only water reactor design among Gen-IV reactors. Preliminary study shows that the thermal efficiency can be as high as 45% for SCWR comparing with traditional reactors which have the thermal efficiencies around 30%. The latest design features together with the software simulator and safety concerns for SCWR applications are described.